Dog tags - Rosenfelt, David (Rosenfelt, David. Andy Carpenter novels., 2010)
Dog-loving lawyer Andy Carpenter plunges into a high profile murder case in which a rogue German shepherd police dog may be the only hope for its owner, an Iraq war vet and former-cop-turned-thief accused of murder.